Mode in Arabic-English Translation: with Reference to the Quran - Najjar, Ibrahim I.I.; Soh, Bee Kwee; Abu al-Haj, Thabet Ahmad Abdallah (Peoples Friendship University of Russia, 2019)
A rhetorical question has the form of a question but does not perform its function, i.e. does not seek any information but rather, is used to give a specific or rhetoric function such as denial, assertion, testing, equalization and negation. The present study investigates the two English translations that were used in the translation of the Quranic rhetorical questions. In a nutshell, this is a comparative study that aims to discover if the grammatical shifts that had occurred in the two English translations would have an effect on the denial, assertion, testing, and equalization and negation modes of the Quranic rhetorical questions. For this purpose, we had adopted the register theory of Halliday and Hassan (1985) as well as the translation shifts of Catford (1965) in the comparison of the two English translations, namely the Koran Interpreted that was authored by Arberry (1955) and the Noble Quran: English translation of the meanings and commentary as transcribed by al-Hilali and Khan (1996). According to the analyses, the occurrence of grammatical shifts between the two translations had in fact affected the mode of the ST rhetorical questions, their rhetorical meanings and consequently, issues on mode sustenance. Therefore, it can be said that the register theory of Halliday and Hassan (1985) had been a beneficial tool used in the analysis of the translation process. © 2019 Peoples' Friendship University of Russia. All rights reserved.